2022
DOI: 10.33134/njmr.369
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Families and Neo-Liberal Globalisation: Past, Present and Future

Deborah Fahy Bryceson

Abstract: The concept of 'transnational family' coalesced in the context of neo-liberal globalisation during the late 1990s and 2000s. This article traces the social, economic and political forces that have influenced the spread of transnational families throughout the world during the 21st century. Meanwhile, the digital revolution in social media communication and cheapening international travel costs has facilitated transnational family members communication with one another. Examining material exchanges between tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(29 reference statements)
0
2
0
2
Order By: Relevance
“…Additionally, healthcare access, international support networks, and philanthropic activities have become more accessible, allowing families to enhance their well-being and contribute to global causes, further enriching their lives. We found that globalization create economic opportunities (Shah, 2009;Trask, 2013;Wu et al, 2022), opportunities for education and skills development (Bhamani, 2017), cultural enrichment (Magu, 2015, global mobility (Trask, 2013), communication and connectivity opportunities (Bacigalupe & Bräuninger, 2017), healthcare access (Martin et al, 2016), international support network (Furstenberg, 2019), cultural exchange and tolerance (Rahman & Zhang, 2017), family businesses (Wu et al, 2022), and access to information (Bryceson, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, healthcare access, international support networks, and philanthropic activities have become more accessible, allowing families to enhance their well-being and contribute to global causes, further enriching their lives. We found that globalization create economic opportunities (Shah, 2009;Trask, 2013;Wu et al, 2022), opportunities for education and skills development (Bhamani, 2017), cultural enrichment (Magu, 2015, global mobility (Trask, 2013), communication and connectivity opportunities (Bacigalupe & Bräuninger, 2017), healthcare access (Martin et al, 2016), international support network (Furstenberg, 2019), cultural exchange and tolerance (Rahman & Zhang, 2017), family businesses (Wu et al, 2022), and access to information (Bryceson, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Access to information in the context of family research offers significant opportunities for scholars and researchers. Firstly, the digital age has democratized information access, making a wealth of family-related data, studies, and literature available online (Bryceson, 2022). Researchers can access databases, academic journals, government reports, and global surveys, allowing for comprehensive reviews of existing literature and the incorporation of diverse perspectives into their research (Ifigeneia & Dimitrios, 2018).…”
Section: Access To Informationmentioning
confidence: 99%
“…Remessas vão além do envio de dinheiro em si. São importantes ferramentas de manutenção da teia que sustenta grandes movimentos migratórios (Tilly, 2007), com especial importância para manutenção da coesão das relações familiares (Bryceson, 2022). Uma vez que os recursos chegam ao seu destino, há toda uma mobilização de migrantes venezuelanos para auxiliar seus parentes a adquirirem um medicamento ou serviço em saúde em seu país de origem.…”
Section: Arranjos Familiares Transnacionais Em Contextos De Criseunclassified
“…JHPIS -VOLUME 3, NO. 1, MARET 2024 yang lebih baik dan peningkatan mobilitas ekonomi atau keamanan negara yang stabil secara politik (Bryceson 2022).…”
unclassified